Synthesis of Branched Cyclo-Olefin Copolymers Using Neutral α-Sulfonate-β-Diimine Nickel Catalyst - Donghui Li; Lixia Pei; Wenbo Du; Xieyi Xiao; Heng Gao; Handou Zheng; Haiyang Gao (Molecules)
The homopolymerization of norbornene and the copolymerization of norbornene and ethylene were carried out using the neutral α-sulfonate-β-diimine nickel catalyst SD-Ni. The neutral α-sulfonate-β-diimine catalyst is highly active in the homopolymerization of norbornene, producing vinyl-addition polynorbornene (PNB) with a high molecular weight. The copolymerization of norbornene (NB) and ethylene (E) using the catalyst SD-Ni was also investigated. The α-sulfonate-β-diimine catalyst SD-Ni shows distinctive catalytic copolymerization properties to produce high-molecular-weight E-NB copolymers with low norbornene incorporation. Importantly, microstructure analyses confirm that the resultant E-NB copolymers are branched cyclo-olefin copolymers (COCs) with branched polyethylene units.